CORRECTION OF SARCOPENIA IN ELDERLY PATIENTS WITH POST-COVID-19 SYNDROME USING PHYSICAL THERAPY (Rehabilitation and Recreation, 2024)
Purpose – to determine the effectiveness of the developed physical therapy program for the elderly with post-COVID syndrome according to the dynamics of sarcopenia parameters. Material. 108 elderly people were examined. The control group consisted of 33 people who did not suffer from the coronavirus disease. The main group consisted of 75 people who fell ill with coronavirus pneumonia and diagnosed with post-COVID syndrome. The main group 1 consisted of 34 people who underwent rehabilitation in polyclinic conditions according to the general principles of the Protocol for providing rehabilitation care to patients with COVID-19. The main group 2 consisted of 41 patients who underwent recovery according to the developed rehabilitation program, which included therapeutic exercises of various orientations, functional training, independent implementation of the Otago exercise program complex, a course of general massage, ergotherapeutic methods, nutritional recommendations, patient education taking into account the peculiarities of pathogenesis and clinical course of geriatric syndromes. The effectiveness of the program was evaluated according to the dynamics of indicators of the whale dynamometry, Short Physical Performance Battery, Edmonton Frail Scale. The results. In elderly patients with post-COVID syndrome, signs of muscle weakness (according to hand dynamometry), impaired balance (Short Physical Performance Battery), deterioration of activities of daily living (according to the Edmonton Frail Scale) were found. The developed rehabilitation program revealed a statistically significantly better effect on indicators of strength, balance, and the state of physical weakness in comparison with the initial indicators in all studied parameters (р
Keywords: rehabilitation, with post-covid syndrome, old age, geriatric syndromes, pulmonary diseases